Development of E-Practicum Module for Pharmacy Physics Learning - Dhina, Meiry Akmara; Hadisoebroto, Ginayanti; Mubaroq, Sugeng Rifqi (Universitas PGRI Kanjuruhan Malang, 2019)
This research develops learning methods through the development of teaching materials. In addition to this study developes an e-practicum module in one of the subjects in the pharmacy department, namely physics pharmacy. Today, the physics pharmacy practice uses printed module practice in the form of module books. This research intends to make innovation in practical learning. Current educational innovations that are developing in technological innovations, one of which is information technology. The use of information technology is very fast and sophisticated, currently technological computer-based has been developing with software applications that also continue to fulfil the world's needs. The development of this electronic technology can be utilized in educational innovations in practice methods. The printed module practice was developed into a web-based electronic practicum module. The method used in this research is the waterfall model which consists of the main stages of needs analysis, system and software design, system implementation and testing as well as a maintainance. The results of this study are a web-based module-practice named E-mulsi which can be accessed via e-mulsi.com. This application has been tested in one of the pharmacy physics classes and has received positive responses from users not only students but also lecturers because it is easier to use modules and preparation of technology-based reports.